Study of Curriculum 13 in Learning Systems during a Pandemic - Foibe Dahlianti Pasaribu; Gita Novalisa Paska Tarigan; Septi Rahmadni Sinaga; Yovana Prayer Situmeang; Laurensia Masri Perangin Angin (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Studying the Kurikulum 2013 in the Learning System in the Pandemic. The curriculum is the most important thing in the educational process, where the curriculum is used as a reference for educators and students in carrying out learning. The educational curriculum must follow situations and conditions, such as during this pandemic, educational activities are limited, thus requiring teachers and parents to work together in the process of learning activities. Therefore, in this case we need to examine the Kurikulum 2013 in the learning system during this pandemic. Through this paper, we want to know how the learning system in the Kurikulum 2013 works during a pandemic and the challenges and solutions for implementing the curriculum during a pandemic The purpose of writing this article is that we want to examine the problems of learning in dealing with the current pandemic situation. The method used in this article is a qualitative method, where this method is carried out by collecting data from reviewing books, articles, and laws that are collected. The results obtained are that learning activities have been disrupted due to this pandemic, but learning must continue to run by utilizing technology or distance learning applications. The Kurikulum 2013 can still run well with the online learning system, although there are some advantages and disadvantages, but the Kurikulum 2013 can keep up with the times.